A study on the factors affecting adoption of the internet banking among sabahan in Kota Kinabalu Sabah - Jamran, Nurfarianeh (2013)
This study aims to identify the factors that influence Sabahan towards Internet Banking at Kota Kinabalu area. 150 sets of questionnaire distributed among Sabahan people. The distribution is on simple random sampling. The independent variables used are perceptions towards internet Banking and demographics factors and the dependent variable is adoption of internet banking. To identify the significant of independent and dependent variables Multiple Regression Analysis will be used. From 150 sets of questionnaires distributed but only 70 sets is fully completed. The finding states that the perceptions and demographics factors have a significant with the adoption of internet banking. Meanwhile, the significant of perceptions and adoption of internet banking has reverse relationships of Sabahan people in Kota Kinabalu area.